A Quiet Place - Wood, Douglas; 1951-; Andreasen, Dan (New York, 2002)
Text and illustrations describe some of the special places that one can go to be quiet and alone and to imagine, such as a woods, a seashore, a library, or inside oneself.
Accelerated Reader AR